2008
DOI: 10.2106/jbjs.g.01608
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Disc Arthroplasty Compared with Arthrodesis for the Treatment of Myelopathy

Abstract: We found that patients in both the arthroplasty and arthrodesis groups had improvement following surgery; furthermore, improvement was similar between the groups, with no worsening of myelopathy in the arthroplasty group. While the findings at two years postoperatively suggest that arthroplasty is equivalent to arthrodesis for the treatment of cervical myelopathy for a single-level abnormality localized to the disc space, the present study did not evaluate the treatment of retrovertebral compression as occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
101
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 20 publications
0
101
0
5
Order By: Relevance
“…A cadaveric biomechanical study of the cervical spine characterized this motion compensation after anterior cervical discectomy and fusion at different levels 10 . In vitro studies supported the conclusion that anterior cervical discectomy and fusion at the operated level increases intersegmental motion as well as load and intradiscal pressure at the adjacent levels and may induce progressive disc degeneration at these levels 9 . Some studies have also shown a relationship between the loss of range of motion at the operated level after this procedure and persistent neck pain, poor functional recovery, cervical instability, or even development of accelerated adjacent-level disc degeneration, which is one of the main reasons for the failure of this treatment 2,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A cadaveric biomechanical study of the cervical spine characterized this motion compensation after anterior cervical discectomy and fusion at different levels 10 . In vitro studies supported the conclusion that anterior cervical discectomy and fusion at the operated level increases intersegmental motion as well as load and intradiscal pressure at the adjacent levels and may induce progressive disc degeneration at these levels 9 . Some studies have also shown a relationship between the loss of range of motion at the operated level after this procedure and persistent neck pain, poor functional recovery, cervical instability, or even development of accelerated adjacent-level disc degeneration, which is one of the main reasons for the failure of this treatment 2,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 59%
“…A nterior cervical discectomy and fusion is one of the most commonly performed spinal procedures 8,9 . The clinical outcome of this procedure is satisfactory in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the weaknesses of the abovementioned studies included small case numbers, lack of a control group, or relatively short follow-up. Riew et al analyzed data from a cohort of patients with myelopathy 29 who were enrolled in the US FDA-IDE trials of the There are a few common conditions other than DDD that cause CSM (ossification of posterior longitudinal ligament [OPLL]), hypertrophy of the ligamentum flavum, or kyphotic deformity). However, similar to the FDA IDE trials, the present study did not include pathologies other than spondylosis and DDD.…”
Section: Discussionmentioning
confidence: 99%
“…23 Tension applied by dentate ligaments preferentially stretches the lateral aspect of the spinal cord on neck flexion, 17 which corresponds to lateral column atrophy noted in autopsy studies. Segmental OPLL has been shown to permit abnormal mobility between adjacent VB segments, with a range of motion > 35° at C1-7 associated with progressive myelopathy.…”
mentioning
confidence: 98%